1992
DOI: 10.1002/micr.1920130606
|View full text |Cite
|
Sign up to set email alerts
|

Use of fibrin glue to minimize bleeding of microvascular repairs in hypertensive rats

Abstract: The purpose of this study is to describe our technique of applying fibrin glue at the microvascular anastomotic site and to evaluate the effect of fibrin glue on anastomotic hemostasis and patency under various high pressure states using dopamine-induced acute hypertension in rats. A total of 72 male Wistar Kyoto rats, 10 weeks old, were used in this study. Under urethane anesthesia, end-to-end anastomosis of the left femoral artery was performed using 10-0 nylon suture by the standard interrupted suture techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
7

Year Published

1997
1997
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 9 publications
1
5
0
7
Order By: Relevance
“…The possibility of minimizing the number of sutures required per anastomosis was also evidenced in other studies, where 33-50% of suture reduction was successfully achieved. 1,8,12,13 On the other hand, Sagi et al 6 and Moskovitz et al 9 tried to perform anastomoses in the femoral and inferior epigastric arteries using only fibrin glue, without any suture, but the results were catastrophic due to acute anastomosis disruption and high rate of aneurysm formation. A common issue of these two studies was that they relied solely on the fibrin glue to support the anastomoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of minimizing the number of sutures required per anastomosis was also evidenced in other studies, where 33-50% of suture reduction was successfully achieved. 1,8,12,13 On the other hand, Sagi et al 6 and Moskovitz et al 9 tried to perform anastomoses in the femoral and inferior epigastric arteries using only fibrin glue, without any suture, but the results were catastrophic due to acute anastomosis disruption and high rate of aneurysm formation. A common issue of these two studies was that they relied solely on the fibrin glue to support the anastomoses.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first experiments with fibrin glue application in microvascular anastomoses by Pearl et al 1 and Matras et al 2 in 1977, several authors reported its use to minimize the number of sutures and to decrease the surgery time required to perform microvascular anastomosis. [3][4][5][6][7][8][9][10][11][12][13] Most of them achieved very satisfactory results, with significant reduction of sutures and anastomosis time, yet maintaining adequate patency rates. Despite the supporting evidences in the experimental literature, the clinical application of fibrin glue in microvascular anastomoses is still limited to a few case series.…”
mentioning
confidence: 99%
“…[52][53][54][55][56][57] However, concerns regarding the inherent thrombogenicity of these products and the potential for triggering intraluminial thrombosis exist. 58 Although promising animal studies have been published, [59][60][61][62][63][64] few clinical series exist. At least one large series of free tissue transfers in breast reconstruction (n 5 349) reports use of thrombin-based glues with no apparent increase in anastomotic failure.…”
Section: Adhesivesmentioning
confidence: 98%
“…[5][6][7] Of these, fibrin adhesives are the most widespread hemostatic agent in use today. 1,3 It has been suggested that at least four criteria should be met if the hemostatic/adhesive agent is to be clinically useful 8 : biocompatibility, useful in a moist environment, no interference with healing, and inherent adhesive properties that allow it to remain where placed. Even though fibrin sealants have many useful qualities they also have drawbacks including the potential for transmission of viral diseases which, although very low is not zero (see review by Jackson, MR).…”
mentioning
confidence: 99%